Why publish in the SA Heart Journal - Journal, SA Heart (SA Heart Journal, 2017)
<span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: italic; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #fbfbf3; display: inline !important; float: none;">SA Heart Journal - Journal of the South African Heart Association.